Acute physiological effects on macromolecule digestion following oral ingestion of the enzyme blend Elevase® in individuals that had undergone an ileostomy, but were otherwise healthy—a randomized, double blinded, placebo-controlled exploratory study - Mazhar, Shahneela; Simon, Annie; Colom, Joan; Khokhlova, Ekaterina; Buckley, Martin; Phipps, Christopher; Deaton, John; Rea, Kieran (Frontiers in Nutrition, 2024)
Digestive enzymes can selectively degrade proteins, carbohydrates and lipids; and their supplementation alongside food may accelerate the breakdown of complex food matrices, facilitate greater nutrient absorption, decrease food sensitivities and aid in the management of certain disease states. Several intrinsic and extrinsic factors govern food digestion and for every individual this phenomenon is unique. This study was conducted as a randomised, crossover, placebo-controlled design where each participant served as their own control. This post-hoc analysis investigated the impact of a dietary enzyme supplementation blend known as Elevase ® on dietary macromolecule digestion in samples from otherwise healthy participants that had previously undergone a small bowel resection, resulting in an ileostomy (NCT04489810). This is the first time this study-paradigm has been used for the assessment of in vivo dietary breakdown following enzyme supplementation. Arguably, this technique offers superior data when compared to that generated in artificial gut digestion models, preclinical animal models, or indeed conventional clinical studies using stool analyses, as it allows real-time access to samples in situ in the small intestine where the majority of nutritional absorption takes place. It was demonstrated that after 4 hours, Elevase ® significantly increased monosaccharide levels (predominantly glucose and fructose) in the ileostomy samples taken from the same individuals on the same diet on a different day. In addition, the bile salt taurohyodeoxycholic acid was also increased, suggesting a physiological host response to the macromolecule digestion induced by the Classification: Internal enzymatic blend. Overall, these findings suggest Elevase ® could accelerate food digestion and potentially increase nutrient availability from the diet.